New genus and species of Delphacini (Hemiptera: Delphacidae) from a salt marsh in northern Chile - Campodonico, Juan F.; Coccia, Cristina (Zootaxa, 2019)
Salinesia atacamensis gen. et sp. nov. is described from a coastal wetland of Atacama Region, Chile. It is characterized by the small size (males < 2 mm), dorsal side concolorous, with lateral carinae of pronotum reaching hind margin, armature of male pygofer narrow and not produced, phallus curved ventrad, and abdominal segment X of male without processes.